2021
DOI: 10.5858/arpa.2021-0118-oa
|View full text |Cite
|
Sign up to set email alerts
|

Why Choose a Pathology Career?

Abstract: Context.— There is a global decline in medical graduates pursuing pathology careers, resulting in a broadening gap between workforce demand and supply. Objective.— To determine causes of low popularity of pathology as a career and develop strategies to avoid a workforce crisis. Design.— An online survey was distributed and yielded 1247 responses, including 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…Medical school education provides an excellent opportunity to expose future health care professionals to the content and day-to-day practice of the specialty. This is critical, as one of the most commonly cited reasons in surveys for not choosing pathology as a specialty is lack of exposure and knowledge of the subject matter among medical students [ 3 ]. Factors that influence specialty choice among current students include interest in the field, intellectual challenge, work-life balance, career opportunities, professional standards, workplace atmosphere, and workplace prestige [ 14 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medical school education provides an excellent opportunity to expose future health care professionals to the content and day-to-day practice of the specialty. This is critical, as one of the most commonly cited reasons in surveys for not choosing pathology as a specialty is lack of exposure and knowledge of the subject matter among medical students [ 3 ]. Factors that influence specialty choice among current students include interest in the field, intellectual challenge, work-life balance, career opportunities, professional standards, workplace atmosphere, and workplace prestige [ 14 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…By 2022, approximately 60% of practicing pathologists were 50 years of age and older [ 2 ]. Studies have shown that medical students often overlook a career in pathology due to a lack of interest and understanding of the subject matter [ 3 ]. Medical education offers the opportunity to inspire future generations of medical students for the subject of pathology in all its variety.…”
Section: Introductionmentioning
confidence: 99%
“…The pathologist also elicited less favorable perceptions in the video as compared to in the transcript. These differences also likely reflect the acting choices made by the actor, who properly reflected the delivery that such testimony would likely entail, particularly given that pathologists and those medical students interested in pathology are more likely to identify as introverted (Fielder et al, 2022 ). There were some significant differences as a function of defendant race, such that both the police officer and the prosecutor yielded more positive perceptions when the defendant was White, while the defense yielded more positive perceptions when the defendant was Black.…”
Section: Discussionmentioning
confidence: 99%
“…13 Despite efforts to integrate pathology into undergraduate medical education curriculum and create pipelines into pathology, there are nearly 1% of medical students going into pathology with many students citing misinformation about pathology careers/ the job market as dissuading. [14][15][16][17] Thus, TikTok can be a useful tool to show future pathologists the realities of forensics and pathology while also being an accessible point of contact for questions. These young users are likely to initiate communication with content creators through comments and direct messages.…”
mentioning
confidence: 99%
“…A recent study by Holloman et al found that over half of medical students who responded to the survey used social media to research pathology, with a minority stating that the information they found to be encouraging 13 . Despite efforts to integrate pathology into undergraduate medical education curriculum and create pipelines into pathology, there are nearly 1% of medical students going into pathology with many students citing misinformation about pathology careers/the job market as dissuading 14–17 . Thus, TikTok can be a useful tool to show future pathologists the realities of forensics and pathology while also being an accessible point of contact for questions.…”
mentioning
confidence: 99%